Resist : 35 profiles of ordinary people who rose up against tyranny and injustice - Chambers, Veronica (HarperCollins, 2018)
"Before they were activists, they were just like you and me. From Frederick Douglass to Malala Yousafzai, Joan of Arc to John Lewis, Susan B. Anthony to Janet Mock these thirty-five profiles of remarkable figures show us what it means to take a stand and say no to injustice. This inspiring collection profiles men and women who resisted tyranny, fought the odds, and stood up to bullies that threatened to harm their communities. Along with their portraits and most memorable quotes, their stories will inspire you every single day to speak out and rise up."--Page [2] of cover.